Study Analysis of Character Values in the Thematic Book for Grade III Elementary School Students - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Putri Fadillah (Ta'dib, 2023)
These character values are 18 contained in the Thematic Book for Grade III Elementary School Students which can be studied by educators through analysis. This study aims to examine the analysis of material content in the Thematic Book for Grade III Elementary School Students Curriculum 2013 Revised Edition 2018 which contains character values. This research uses a qualitative approach with a type of document study. The subject in this study is the researcher himself. The objects used in this study are contained in data and data sources. This research data is in the form of 18 character values in the 2013 Curriculum. The data source is in the form of Thematic Books for Grade III Elementary School Students Curriculum 2013 Revised Edition 2018. The data is analyzed by content analysis method. The content analysis techniques used, namely unitizing sampling, recording, reducing, inferring, and narrating. The results of the analysis of character values studies in the Thematic Book for Grade III Elementary School Students Curriculum 2013 Revised Edition 2018 are religious, honest, tolerance, discipline, hard work, creative, independent, respect achievements, democratic, curiosity, national spirit, love of the country, friendly/communicative, love peace, love of reading, care for the environment, care for social, and responsible. By reviewing the contents of the Thematic Book for Class III Students Curriculum 2013 Revised Edition 2018, it is hoped that educators can find out the character values contained in the book and be able to help students form student character values in each of their learning activities.